Perancangan Interior Cafe Salon Di Malang - Celia Magaski Djuari; Sriti Mayang Sari (Intra, 2015)
Malang City has good prospect in the culinary fields such as cafes and salon, because the consumptive lifestyle as become a trend in Malang City. Cafe  is often used as a place to gather and meet the culinary needs, while salon is often used as a place to let saturation off and body pampering. These perspectives brings Malang into a need of a space to fulfill consumer consumptive pattern and to release saturation in Malang City. This design uses the concept of "Care and Relax". The aim of this concept is to create a space needed by the people which is a place that provides comfortable, serene and relax interior for the people inside. This concept also functions to give warm athmosphere. The application of care in the design is by proximity, protection, openess, and attention while the application of relax in the design is by calmness, roomy and light.